Phenotypic and genotypic detection of ESBL-producing E. coli isolates from chicken skin in Bosnia and Herzegovina - Vildana Hadžić-Hasanović; Anesa Jerković-Mujkić; Ermin Hasanović; Azra Bačić; Mirsada Hukić (Medicinski glasnik, 2020)
Aim: To identify E. coli from chicken meat, establish their antibiotic resistance profiles and to confirm ESBL isolates with real time PCR, as well as to identify risk factors and farming practice associated with the antimicrobial resistance E. coli. Methods: The study included 100 chicken skin samples collected randomly from retail supermarkets, butcheries and slaughterhouses. Disk susceptibility testing was performed using the Kirby-Bauer method. Detection of ESBL-producing isolates was performed with double disk synergy test. Molecular analysis of phenotypic ESBL-producing Escherichia coli strains was performed at 7500 real time PCR System. Molecular-genetic analysis included detection of CTX-M 1, 2, and 9 gene families and mutations in the TEM and SHV encoding extended spectrum ?-lactamases. Results: Prevalence of the phenotypic ESBL-producing E. coli isolates was 29%, and they exhibited remarkable sensitivity to carbapenems (100%) as well as to amikacin (93.10%). All ESBL-producing strains were multidrug resistant. Molecular analysis was performed as the final confirmation of the production of extended spectrum ?-lactamases for 24 isolates out of 29 phenotypicaly ESBL-producing E. coli isolates. Conclusion: It is important to pay attention to people's awareness of bacterial antimicrobial resistance in food chain, as well as to understand its effects on human health and the environment. Phenotypic and molecular analysis demonstrated the presence of ESBL-producing E. coli isolates from chicken skin samples.
Keywords: antimicrobial resistance; food safety; veterinary medicine